“E o verbo se fez rede” uma análise da circulação do “católico” em redes comunicacionais online - Sbardelotto, Moisés (Universidade do Vale do Rio dos Sinos, 2016)
With the advancement of digital mediatization, the Catholic Church and society in general develop new modes of communication on the internet, in which there is a diverse and wide-spread network of relationships between symbols, beliefs, and practices linked to Catholicism, the so-called “Catholic.” From this context, this thesis analyzes the way in which the mediatic processes of circulation of the “Catholic” organize themselves in online communicational net-works that emerge in sociodigitais platforms, like Facebook and Twitter. The analysis is done through a multiple case study, combined with gestures of lurking and semi-structured inter-views done with responsible of the Catholic communication on the Vatican and Brazil, from a Catholic supra-institutional level (the @Pontifex_pt account on Twitter); a Vatican institu-tional level (Rádio Vaticano – Programa Brasileiro page on Facebook); a Brazilian socio-institutional level (Jovens Conectados page on Facebook); and a Brazilian peripheral minority level (Diversidade Católica page on Facebook). From specific questions and propositions, the axes of theoretical articulation and tension reflect on the concepts of mediatization; digital mediatization; a digital mediatization of religion. Then it analyses the four empirical cases around the networked circulation of the “Catholic”, from the interfaces, protocols, and recon-nections observed in each case critically interpreting the processes involved on digital mediati-zation of religion in three different angles of inferences. First, in the context of digital media-tization, it examines the emergence of online communicational networks, which articulates cir-cuits and feeds the circulatory flow. Second, within the context of the networked mediatic circulation, it finds the emergence of a connectial dispositif, i.e., a complex of interrelation-ships between techno-symbolic (interfaces), socio-technical (protocols), and socio-symbolic processes (reconnections) which, in a inter-retroactive form, delimit, condition, and condense networked religious practices. Third, in the context of the reconstruction of the “Catholic”, it points to the emergence of a new communicational religious interagent, the “lay-amateur”, and of communicational heresies, by which occurs the invention/production of something new (construction) and the experimentation/transformation of something already existing (decon-struction) around Catholicism. In conclusion, it suggests the emergence of a “religion (in) common,” marked by a communicatively shared, symbolic-religious know-how and power-of-doing to the promotion of experiences; the establishment of beliefs; and the configuration of religious practices in contemporary societies.
Keywords: Midiatização; Internet; Facebook; Twitter; Religião; Mediatization; Religion; ACCNPQ::Ciências Sociais Aplicadas::Comunicação